(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
India has growth prospect for retail industry with a huge number ofconsumers and other favorable factors. But India’s retail market remainslargely off-limits to large international retailers like Wal-Mart, Tesco andCarrefour. Opposition to liberalizing FDI in this sector raises concerns aboutemployment losses, unfair competition resulting in large-scale exit ofincumbent domestic retailers and infant industry arguments to protect theorganized domestic retail sector that is at a nascent stage. In 2012 the IndianGovernment approved proposal of 100 percent FDI inretailing in India subject to certain conditions.Though this proposal is being hailed byglobal retail giants, which until now have been involved in only wholesale cash and carry distribution in India and have been longing for entry into the Indian retail market foryears. The proposal has receivedvehement opposition from a spectrum of political parties in India, many of themurging for a reversal of the proposal. As a result, the Indian government has stalled the implementation of this proposalwhich has temporarily washed off the wishes of the global retail players awaiting a bite of the Indian retail market. This paper attempts to study the present status of FDI inretailing sector in India and the impacts of FDI on various concerned segments.